2001
DOI: 10.1093/nar/29.2.464
|View full text |Cite
|
Sign up to set email alerts
|

Conserved stem-loop structures in the HIV-1 RNA region containing the A3 3' splice site and its cis-regulatory element: possible involvement in RNA splicing

Abstract: The HIV-1 transcript is alternatively spliced to over 30 different mRNAs. Whether RNA secondary structure can influence HIV-1 RNA alternative splicing has not previously been examined. Here we have determined the secondary structure of the HIV-1/BRU RNA segment, containing the alternative A3, A4a, A4b, A4c and A5 3' splice sites. Site A3, required for tat mRNA production, is contained in the terminal loop of a stem-loop structure (SLS2), which is highly conserved in HIV-1 and related SIVcpz strains. The exon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 40 publications
6
78
0
Order By: Relevance
“…Inefficient splicing of the HIV-1 genome is required to preserve a pool of unspliced and singly spliced transcripts, to be transported across the nuclear membrane via the Rev/RRE dependent pathway+ Besides having suboptimal splice sites, exonic and intronic sequences in the tat pre-mRNA function as binding sites for cellular factors of the hnRNP A/B and hnRNP H classes, which leads to further inhibition of splicing (Amendt et al+, 1994(Amendt et al+, , 1995Staffa & Cochrane, 1994, 1995Si et al+, 1997Si et al+, , 1998Caputi et al+, 1999 Our computer predictions and probing results are consistent with the existence of three major stem loop structures, SL1, SL2, and SL3, of which SL1 and SL3 are conserved in M-type HIV-1+ The ISS and the ESS3 are positioned within SL1 and SL3, respectively, whereas the SL2 harbors a GAA repeat at positions 8420-8430, which is part of the degenerate SF2/ASF-dependent enhancer element ESE3 (Mayeda et al+, 1999;Tange & Kjems, 2001)+ This GAA repeat is highly accessible to chemical modifications by DMS/DEP and single-strand specific RNase cleavage (Fig+ 2A, B), consistent with these sequences acting as binding sites for cellular splicing proteins including hnRNP A1 and presumably also SF2/ASF+ In contrast, we found that S3, which is the functionally most hnRNP A1 responsive site of the ISS, was less accessible to enzymatic probing reagents and situated in a helix structure adjacent to an internal bulge+ Intriguingly, this structure is very similar to the recently reported secondary structural context of the ESS2 (Jacquenet et al+, 2001b)+ The functional significance of this structure is supported by the observation that this base-pairing scheme can form in all investigated M-group viruses (Fig+ 3)+ Another similarity between the ISS and the ESS2 is the appearance of a base-paired UAG element immediately upstream, which corresponds to the S2 sequence of the ISS (Jacquenet et al+, 2001b; this report)+ Modulation of hnRNP A1 binding by RNA structure hnRNP A1 has originally been reported to have a general nonspecific RNA-binding activity, although several reports have specified RNA sequences that are bound by hnRNP A1 with 10-1,000-fold increased affinity (Swanson & Dreyfuss, 1988;Buvoli et al+, 1990;Matunis et al+, 1993;Burd & Dreyfuss, 1994;Mayeda et al+, 1994Mayeda et al+, , 1998Chabot et al+, 1997;Blanchette & Chabot, 1999;Caputi et al+, 1999;Del Gatto-Konczak et al+, 1999;…”
Section: Discussionsupporting
confidence: 86%
“…Inefficient splicing of the HIV-1 genome is required to preserve a pool of unspliced and singly spliced transcripts, to be transported across the nuclear membrane via the Rev/RRE dependent pathway+ Besides having suboptimal splice sites, exonic and intronic sequences in the tat pre-mRNA function as binding sites for cellular factors of the hnRNP A/B and hnRNP H classes, which leads to further inhibition of splicing (Amendt et al+, 1994(Amendt et al+, , 1995Staffa & Cochrane, 1994, 1995Si et al+, 1997Si et al+, , 1998Caputi et al+, 1999 Our computer predictions and probing results are consistent with the existence of three major stem loop structures, SL1, SL2, and SL3, of which SL1 and SL3 are conserved in M-type HIV-1+ The ISS and the ESS3 are positioned within SL1 and SL3, respectively, whereas the SL2 harbors a GAA repeat at positions 8420-8430, which is part of the degenerate SF2/ASF-dependent enhancer element ESE3 (Mayeda et al+, 1999;Tange & Kjems, 2001)+ This GAA repeat is highly accessible to chemical modifications by DMS/DEP and single-strand specific RNase cleavage (Fig+ 2A, B), consistent with these sequences acting as binding sites for cellular splicing proteins including hnRNP A1 and presumably also SF2/ASF+ In contrast, we found that S3, which is the functionally most hnRNP A1 responsive site of the ISS, was less accessible to enzymatic probing reagents and situated in a helix structure adjacent to an internal bulge+ Intriguingly, this structure is very similar to the recently reported secondary structural context of the ESS2 (Jacquenet et al+, 2001b)+ The functional significance of this structure is supported by the observation that this base-pairing scheme can form in all investigated M-group viruses (Fig+ 3)+ Another similarity between the ISS and the ESS2 is the appearance of a base-paired UAG element immediately upstream, which corresponds to the S2 sequence of the ISS (Jacquenet et al+, 2001b; this report)+ Modulation of hnRNP A1 binding by RNA structure hnRNP A1 has originally been reported to have a general nonspecific RNA-binding activity, although several reports have specified RNA sequences that are bound by hnRNP A1 with 10-1,000-fold increased affinity (Swanson & Dreyfuss, 1988;Buvoli et al+, 1990;Matunis et al+, 1993;Burd & Dreyfuss, 1994;Mayeda et al+, 1994Mayeda et al+, , 1998Chabot et al+, 1997;Blanchette & Chabot, 1999;Caputi et al+, 1999;Del Gatto-Konczak et al+, 1999;…”
Section: Discussionsupporting
confidence: 86%
“…Plasmids Used in This Study-pLD-C2, pLD-C3, and pLD-L3-U1 constructs, used for production of the C2, C3, and L3-U1 transcripts, were described previously (11,23,24). To build the plasmid pLD-C1, two DNA fragments were generated by PCR amplifications of plasmid pBRU3 (42) containing the HIV-1 BRU/LAI complete cDNA (GenBank TM accession number K02013).…”
Section: Methodsmentioning
confidence: 99%
“…PCR products were quantified using ImageQuant (Amersham Biosciences). The fractionated cDNAs were identified by reference to previous data on HeLa cells transfected with plasmid ⌬PSP (11,24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations